Penerapan Etika Bisnis Islam di Warung Makan Ibu Matus: Studi di Kelurahan Ujung Piring, Kecamatan Bangkalan, Kabupaten Bangkalan - Romdhoni, Wildhan (Program Studi Hukum Ekonomi Syariah, 2023)
Starting and running a business must be based on ethics, because the implementation of business ethics will lead to noble goals, both in the form of material and immaterial profits. In Islamic economics, the vision and mission of business activities are not only profit-oriented, but also prioritize the benefits of a product and the blessings in obtaining profits. In fact, in the midst of society, there are still shifts in doing business which are not in accordance with the commands of sharia. Therefore, this paper discusses the implementation of business in one of the food stalls in Ujung Piring Village, Bangkalan District, Bangkalan Regency, namely Warung Makan Ibu Matus. The study in this paper is a field research with data acquisition through observation and interviews as the primary data. Then the results of the data are analyzed descriptively which is associated with secondary data, namely the principles of business ethics contained in fiqh books, and other literature. The result of this article is that Warung Makan Ibu Matus has integrated all the principles of Islamic business ethics well, supported by positive responses from its consumers. This confirms that these principles are not only religiously relevant, but also have a positive impact in the context of business and relationships with consumers.